(3eYGde GdJfRjds - (3GdMSjf Hf eSYhO Hf eMeO, GdaqQGA, Ch GHf GdnanqQGA, CHh eMeO, hjdbH HeMjj GdSqfI, GdHZhj,J (B510 (3g` s
(3ChdgG (B:s
(3ShQI GdYfcHhJ ecfg HSf Gddg GdQMef GdQMje GdeQ CMSH GdfGS Cf jJQchG HZjQ GMJHGQ hdG GHJdGA s
(3BNQgG (B:s
(3abGd QShd Gddg Udi Gddg Ydjg hSde ajfG UdM GdefPQjf Ke cQQ eG PcQ JCcjO GdhYO Edi SHMGf QHc QH GdYRI YeG SUahf hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B259 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B61s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1726s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs